2015
DOI: 10.1111/1541-4337.12146
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Fava Bean as Future Protein Supply to Partially Replace Meat Intake in the Human Diet

Abstract: Legumes have the potential to support global protein production by partially replacing meat and dairy products in the human diet. This will not only help meeting the increasing worldwide demand for proteins, but could contribute towards mitigating the threat imposed to the environment by current agricultural practices in higher-economy countries (dependence on fossil fuel energy and harmful emissions). Among the legumes, fava bean (Vicia faba L.) is a valuable crop. It is a rich source of proteins, fiber, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
173
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(181 citation statements)
references
References 159 publications
3
173
0
5
Order By: Relevance
“…Up to date, the most common industrial and domestic food processing procedures mostly affected the native β-glucosidase activity of faba bean and reduced the content of vicine and convicine212. However, the conversion of vicine and convicine into their toxic derivatives is possible via β-glucosidases of the small intestine, the same involved in the absorption and metabolism of dietary (iso)flavonoid glucosides23.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, the most common industrial and domestic food processing procedures mostly affected the native β-glucosidase activity of faba bean and reduced the content of vicine and convicine212. However, the conversion of vicine and convicine into their toxic derivatives is possible via β-glucosidases of the small intestine, the same involved in the absorption and metabolism of dietary (iso)flavonoid glucosides23.…”
Section: Discussionmentioning
confidence: 99%
“…This is despite grain legumes representing a significant source of protein for food (Vaz Patto et al, 2014; Multari et al, 2015) and feed (Jezierny et al, 2010; Koivunen et al, 2014), and legume cultivation reducing the need for N fertilizer even for subsequent crops in the rotation (Preissel et al, 2015). Recent studies have identified a comparative lack of breeding investment in Europe to improve grain legume adaptation to local agro-climatic conditions and management techniques (Annicchiarico and Iannucci, 2008; Lizarazo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Faba bean cultivars used for dry grain production leave a considerable amount of harvest residues, mostly in the form of thick dry stems, that are suitable for green manure; because their low lignin and other harder degradable compounds positively affects the release of nitrogen from the biomass in the soil, thus increase its fertility and have long-term positive impacts upon succeeding crops. In recent years faba bean has been widely used in ecological agriculture (СемТоргЭкспо 2011Multari et al, 2015).…”
Section: Faba Bean (Vicia Faba L)mentioning
confidence: 99%